Low Levels of Vitamin D were Associated with Coagulopathy among Hospitalized Coronavirus Disease-19 (COVID-19) Patient: a Single Centered Study in Indonesia - Susianti, Hani; Wahono, Cesarius Singgih; Rahman, Perdana Aditya; Pratama, Mirza Zaka; Wulanda, Indah Adhita; Hartanti, Khoirunisah Dwi; Dewi, Elvira Sari; Handono, Kusworini (Journal of Medical Biochemistry, 2021)
Background: This study was aimed to explore the association of vitamin D in the risk of coagulopathy in coronavirus disease-19 (COVID-19). Methods: Clinical and laboratory findings were obtained from 50 confirmed COVID-19 patients hospitalized in Saiful Anwar General Hospital, Malang, Indonesia since September to November 2020. Thrombotic events during hospitalization were recorded and ISTH disseminated intravascular coagulation (DIC) score was used for the classification of overt DIC. Hypovitaminosis D was defined by serum vitamin D level <20 ng/ml. Results: Among 50 patients, 42 (84%) had hypovitaminosis D and 6 (12%) developed thrombotic events. Vitamin D levels were lower in patients with thrombotic events (p=0.015), D-dimer >2 mg/L (p=0.006), ISTH DIC score ≥5 (p=0.020), admitted on ICU (p=0.002), and non-survivor groups (p=0.007). Multivariate analysis for the risk in increased levels of D-dimer showed low vitamin D as the only significant risk factor with OR 1.8 (1.2-4.4), p=0.034. Low vitamin D also increased the risk for developing overt DIC with OR. 5.4 (1.0-30.2), p=0.039. Vitamin D level had negative correlations with ferritin (R=-0.316, p=0.044) and CRP (R=-0.530, p=0.000). Conclusion: In conclusion, low level of vitamin D was found in the majority of hospitalized COVID-19 patients and might be associated with the development of the coagulopathy.